1976
DOI: 10.1111/j.1545-5300.1976.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Acknowledgment in the Family Rorschachs of Families With a Child at Risk for Schizophrenia

Abstract: Lack of acknowledgment, a characteristic of the direct interactions of families of schizophrenics, was found also to characterize the Family Rorschach interactions of families whose disturbed, non-psychotic adolescents were assessed at high risk for schizophrenia on the basis of parental communication deviance. The same high-risk families had unbalanced interaction patterns as reflected in three measures of family structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…A closer examination of the scorers' descriptions of the communication patterns shows that the Group S families, in comparison with the Group N families, were characterized by (a) less ability or willingness to listen to and take into account what the others said; (b) less ability or willingness to take the perspective of the other (both [a] and [b] are closely connected to degree of egocentrism/decentration); (c) less adequate confirmations of each other; (d) more pseudo‐agreement. These findings are much in line with what has been reported from other studies conducted under varying conditions (30, 38, 50, 74).…”
Section: Discussionsupporting
confidence: 93%
“…A closer examination of the scorers' descriptions of the communication patterns shows that the Group S families, in comparison with the Group N families, were characterized by (a) less ability or willingness to listen to and take into account what the others said; (b) less ability or willingness to take the perspective of the other (both [a] and [b] are closely connected to degree of egocentrism/decentration); (c) less adequate confirmations of each other; (d) more pseudo‐agreement. These findings are much in line with what has been reported from other studies conducted under varying conditions (30, 38, 50, 74).…”
Section: Discussionsupporting
confidence: 93%
“…Family communication was sampled using the Consensus Rorschach method (Loveland, Wynne, & Singer, 1963). Its usefulness as a family interaction task for this kind of research has been shown in numerous studies (Herman & Jones, 1976; Shapiro & Wild, 1976; Tienari, 1991; Wichstrøm & Holte, 1991a, b). In the URCAFS study it was administered in two phases.…”
Section: Methodsmentioning
confidence: 99%
“…The research has shown (a) reduced predictability of which family members will speak (Mishler & Waxier, 1975); (b) a higher rate of balanced triadic interaction than dyadic interaction in normal families compared to disturbed families (Herman & Jones, 1976); (c) balanced rates of frequency of speech among nondisabled family members (Leighton, Stollack, & Ferguson, 1971;Murrell, 1971); and (d) increased frequency of intrusions into the discussion of nondisabled families (Leonard, Beaulieu, & Embry, 1965;Mishler & Waxier, 1975).…”
Section: Family Functioningmentioning
confidence: 97%